A CASE STUDY OF THE STUDENTS’ UNDERSTANDING OF PASSIVE VOICE IN SECOND SEMESTER STUDENTS OF ENGLISH EDUCATIONAL PROGRAM AT INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Masyudi, Masyudi; Hadi, M. Wahyu; Paris, Atika Salman (LPPM Institut Pendidikan Nusantara Global, 2023)
This research deals with the grammar skill that is the students understanding of passive voice. This research is aimed to investigate the students understanding of passive voice at the second semester students of English educational Program at Institut Pendidikan Nusantara Global in academic year 2022/2023, the title is taken by the writer because he wants to answer the statement of problem that stated do the students have understanding of passive voice. Therefore, the writer proposed to find out whether the second semester students of English educational Program at Institut Pendidikan Nusantara Global have understanding passive voice. In this research the writer gave two kinds of test to the students, the grammar test in multiple choice and modified test is changing the active sentence into passive sentence, the writer took the second semester students as the population that consist of four classes with the total students until 10 students and the writer took all of students as the sample. The result of the investigation showed from 23 students, the students who was classification as good were 8 students and 15 students were classification as low. Arriving at the end of this writing the writer restates the conclusion of research, the achievement level of second semester students of English educational Program at Institut Pendidikan Nusantara Global do not have understanding on passive voice